Effectiveness of augmented feedback on drop landing using baseline vertical ground reaction in female athletes - Heinert, B.; Rutherford, D.; Kernozek, T. W. (International Journal of Athletic Therapy & Training, 2022)
Context: Targeted training using augmented feedback to influence landing mechanics may be beneficial to athletes. Purpose: Examine how augmented feedback may influence vertical ground reaction force (VGRF) and improve knee valgus in females that display greater VGRF during drop landings. Main Results: Two hundred and forty female athletes participated and were divided into quartiles based on VGRF. Reductions in VGRF and knee valgus were seen across all quartiles with augmented feedback. Greatest reductions were found in the quartile with the largest baseline VGRF. Interpretation: Augmented feedback may be more effective in reducing VGRF and improving knee to ankle ratio in female athletes that have greater baseline VGRF.